1986
DOI: 10.1258/002367786780865160
|View full text |Cite
|
Sign up to set email alerts
|

Exophthalmos in ageing rats with Harderian gland disease

Abstract: SummaryExophthalmos was found in aged rats in several longevity studies. Four cases were due to malignant Harderian gland neoplasia whilst others were associated with severe Harderian gland inflammation, less severe inflammation being found in rats without exophthalmos. Keywords: Rats; Harderian gland; Exophthalmos; Corona virus infections; NeoplasmsDuring routine physical examinations of rats in several longevity studies, cases of exophthalmos associated with Harderian gland neoplasia and inflammation were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The PAS stain revealed seromucoid secretion in the ducts which is reported for the lacrimal gland as opposed to the serous Harderian gland function 21 . Also, we could not identify porphyrin crystals in any section: these are described as characteristic contents of the Harderian gland in rodents 22,23 . The histologic diagnosis of interstitial dacryoadenitis was made.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The PAS stain revealed seromucoid secretion in the ducts which is reported for the lacrimal gland as opposed to the serous Harderian gland function 21 . Also, we could not identify porphyrin crystals in any section: these are described as characteristic contents of the Harderian gland in rodents 22,23 . The histologic diagnosis of interstitial dacryoadenitis was made.…”
Section: Discussionmentioning
confidence: 66%
“…The latter is located inferior and anterior to the globe within the orbit 21 . Abnormalities of the Harderian gland may cause exophthalmos 22,23 . Upon histopathologic examination the cystic tissue was determined to derive from the lacrimal gland.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] The biologic behavior of these tumors varies by species. In mice, Harderian gland adenomas are common in the B6C3F1 strain, with a 4.7% incidence in control males and a 3.3% incidence in control females reported in NTP carcinogenicity studies; carcinomas were reported at a rate of 0.7% in both males and females in the same study.…”
Section: Discussionmentioning
confidence: 99%
“…1 The function of the gland is poorly understood; while lubrication of the nictitans and cornea is considered to represent the primary purpose of the gland, other proposed roles of the gland and its secretions in mammals include photoprotective effects of the porphyrins, 1 social signaling through pheromones, 2,3 thermoregulation through contribution to pelage lipids, 1,4 and coordination with the pineal-retinal axis through synthesis of serotonin and melatonin. 1,5 Neoplasms of the Harderian gland have been described in several rodent species, including the mouse, 6 rat, 7,8 hamster, 9 and vole; 10 and a single case report in the ground squirrel. 11 Neoplasms may arise spontaneously or as a result of exposure to a variety of chemical carcinogens.…”
Section: Introductionmentioning
confidence: 99%
“…A less common cause was orbital neoplasia, such as poorly differentiated adenocarcinoma, solid carcinomas, and poorly differentiated sarcoma (Fig. 2) [25].…”
Section: Adnexa and Lacrimal Systemsmentioning
confidence: 99%